2010
DOI: 10.1503/cmaj.091208
|View full text |Cite
|
Sign up to set email alerts
|

Use of antidepressants during pregnancy and the risk of spontaneous abortion

Abstract: ; Centre hospitalier universitaire Sainte-Justine (Nakhai-Pour, Broy, Bérard), University of Montreal, Montréal, Que.; École nationale de la statistique et de l'analyse de l'information (Broy), Rennes, France; and the Ministry of Health and Medical Education (Nakhai-Pour), Tehran, Iran CMAJ 2010. DOI:10.1503/cmaj.091208 Background:The risk of relapse of depression or the diagnosis of some other psychiatric disorders during pregnancy necessitates the use of antidepressants despite possible adverse effects. Whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
86
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 33 publications
5
86
0
8
Order By: Relevance
“…To our knowledge, smoking and maternal BMI are not risk factors for spontaneous abortion, 15 and are thus not confounders in our study. Exposure data based on filled prescriptions might not necessarily reflect actual intake of a medication.…”
mentioning
confidence: 49%
“…To our knowledge, smoking and maternal BMI are not risk factors for spontaneous abortion, 15 and are thus not confounders in our study. Exposure data based on filled prescriptions might not necessarily reflect actual intake of a medication.…”
mentioning
confidence: 49%
“…4 SSRIs have been associated with spontaneous abortion. 5,6 Most of the women stops taking antidepressants (<6 weeks of gestation) because of concerns about teratogenicity. 7 It has been suggested that SSRIs may cause irregular uterine bleeding by reducing serotoninmediated uterine contraction as well as interfering with hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…For smoking and BMI to be confounders, they would need to be associated with both outcome and exposure. Delaney and colleagues 5 have shown that smoking and BMI are not associated with use of NSAIDs that are prescribed or over the counter.…”
mentioning
confidence: 99%
“…They cite their own work as the source for this statement. 5 Not only maternal, but also paternal and environmental exposure to smoking have been reported to be associated with an increased incidence of spontaneous miscarriage. 6 A recent meta-analysis of the effect of BMI on spontaneous abortion reported that patients with a BMI greater than 25 kg/m 2 have significantly higher odds of miscarriage regardless of the method of conception, 7 and evidencebased guidelines for the investigation and treatment of recurrent miscarriage include BMI as a risk factor.…”
mentioning
confidence: 99%